2020
DOI: 10.1038/s41598-020-66885-y
|View full text |Cite
|
Sign up to set email alerts
|

Eco-production of silica from sugarcane bagasse ash for use as a photochromic pigment filler

Abstract: eco-production of silica from sugarcane bagasse ash for use as a photochromic pigment filler prinya chindaprasirt 1,2 & Ubolluk Rattanasak 3 ✉ Sugarcane bagasse is a significant renewable energy source for the sugar and bioethanol industries. Bagasse ash is the waste from the combustion process and is mostly disposed of as landfill. Only a small quantity of bagasse ash is utilized as pozzolan in concrete, and a considerable quantity is left unused due to its high carbon and crystallite content. Generally, baga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 17 publications
3
38
2
Order By: Relevance
“…The biogenic nano silica they successfully prepared from rice husk as the silica source shows the same XRD pattern of amorphous silica. The nanosilica synthesized from sugarcane bagasse also shows a broad XRD peak of 2θ around 23° [48]. These literatures are in line with the current study.…”
Section: Crystalline Property By Xrdsupporting
confidence: 92%
See 1 more Smart Citation
“…The biogenic nano silica they successfully prepared from rice husk as the silica source shows the same XRD pattern of amorphous silica. The nanosilica synthesized from sugarcane bagasse also shows a broad XRD peak of 2θ around 23° [48]. These literatures are in line with the current study.…”
Section: Crystalline Property By Xrdsupporting
confidence: 92%
“…Recently nanostructure silica was extracted through alkali leaching method from various bio-precursors like banana peel, orange peel, coconut husk, wall nut shell and ground nut shell [32]. Sugarcane bagasse ash was promised to be excellent source for silica preparation [33]. Although extensive literature exists on the physical and chemical phenomena of silica produced from sodium silicate precipitated with acids and also from rice husk and other biogenic sources.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that silica extraction from bagasse ash with pretreatment using HCl obtained more silica content when compared without treatment [22]. The reactions that occur include the following [14].…”
Section: Resultsmentioning
confidence: 99%
“…Several silica applications include catalysts, cosmetics, ceramics, cement, pharmaceuticals, and detergents [5,12]. Silica is also commonly applied as a precursor for the synthesis of inorganic and organometal substances, as a coating for electronic and optical materials, as a filler for composites, and as a filler in photochromic pigment [13,14]. Silica has a large pore and surface area that allowed it to be utilized as an adsorbent, such as removing methylene blue dye, Janus Green B, Reactive Black 5, and dimethyl phthalate [15].…”
Section: Introductionmentioning
confidence: 99%
“…For an example, Worathanakul et al [31] pre-treated sugarcane bagasse (i.e., a mixture of fiber and pith) with 3M HCl to produce biogenic silica with a silica content of 89 wt% compared to 94.8 and 94.3 wt% for pith and fiber obtained in this work, respectively. On another study, [32] pre-treated sugarcane bagasse with 1M HCl and obtained an even lower silica content of 66 wt%. In yet another recent study a silica content of 85.6 wt% was obtained from the pre-treatment of sugarcane bagasse with 9% sulfuric acid [33].…”
Section: The Influence Of Leaching On the Chemical And Elemental Compmentioning
confidence: 97%